ChemInform Abstract: Catalytic Asymmetric Bromolactonization Reactions Using (DHQD)2PHAL‐Benzoic Acid Combinations. Issue 14 (8th April 2014) - Armstrong, Alan; Braddock, D. Christopher; Jones, Alexander X.; Clark, Stacy
Abstract The use of benzoic acid as the additive for the bromolactonization of various carboxylic acids in the presence of catalytic amounts of (DHQD)2‐PHAL affords the corresponding lactones with improved enantioselectivity.